Does cross-generational epigenetic inheritance contribute to cultural continuity?. Issue 2 (26th April 2018) - Pembrey, Marcus E
Abstract: Human studies of cross-generational epigenetic inheritance have to consider confounding by social patterning down the generations, often referred to as 'cultural inheritance'. This raises the question to what extent is 'cultural inheritance' itself epigenetically mediated rather than just learnt. Human studies of non-genetic inheritance have demonstrated that, beyond foetal life, experiences occurring in mid-childhood before puberty are the most likely to be associated with cross-generational responses in the next generation(s). It is proposed that cultural continuity is played out along the axis, or 'payoff', between responsiveness and stability. During the formative years of childhood a stable family and/or home permits small children to explore and thereby learn. To counter disruptions to this family home ideal, cultural institutions such as local schools, religious centres and market places emerged to provide ongoing stability, holding the received wisdom of the past in an accessible state. This cultural support allows the growing child to freely indulge their responsiveness. Some of these prepubertal experiences induce epigenetic responses that also transfer molecular signals to the gametes through which they contribute to the conception of future offspring. In parallel co-evolution with growing cultural support for increasing responsiveness, 'runaway' responsiveness is countered by the positive selection of genetic variants that dampen responsiveness. Testing these ideas within longitudinal multigenerational cohorts will need information on ancestors/parents' own communities and experiences (Exposome scans) linked to ongoing Phenome scans on grandchildren; coupled with epigenome analysis, metastable epialleles and DNA methylation age. Interactions with genetic variants affecting responsiveness should help inform the broad hypothesis.